The role of GluN2A and GluN2B NMDA receptor subunits in AgRP and POMC neurons on body weight and glucose homeostasis - Aykut Üner; Gabriel H.M. Gonçalves; Wenjing Li; Matheus Porceban; Nicole Caron; Milena Schönke; Eric Delpire; Kenji Sakimura; Christian Bjørbæk (Elsevier, 2015)
Objective: Hypothalamic agouti-related peptide (AgRP) and pro-opiomelanocortin (POMC) expressing neurons play critical roles in control of energy balance. Glutamatergic input via n-methyl-d-aspartate receptors (NMDARs) is pivotal for regulation of neuronal activity and is required in AgRP neurons for normal body weight homeostasis. NMDARs typically consist of the obligatory GluN1 subunit and different GluN2 subunits, the latter exerting crucial differential effects on channel activity and neuronal function. Currently, the role of specific GluN2 subunits in AgRP and POMC neurons on whole body energy and glucose balance is unknown. Methods: We used the cre-lox system to genetically delete GluN2A or GluN2B only from AgRP or POMC neurons in mice. Mice were then subjected to metabolic analyses and assessment of AgRP and POMC neuronal function through morphological studies. Results: We show that loss of GluN2B from AgRP neurons reduces body weight, fat mass, and food intake, whereas GluN2B in POMC neurons is not required for normal energy balance control. GluN2A subunits in either AgRP or POMC neurons are not required for regulation of body weight. Deletion of GluN2B reduces the number of AgRP neurons and decreases their dendritic length. In addition, loss of GluN2B in AgRP neurons of the morbidly obese and severely diabetic leptin-deficient Lepob/ob mice does not affect body weight and food intake but, remarkably, leads to full correction of hyperglycemia. Lepob/ob mice lacking GluN2B in AgRP neurons are also more sensitive to leptin's anti-obesity actions. Conclusions: GluN2B-containing NMDA receptors in AgRP neurons play a critical role in central control of body weight homeostasis and blood glucose balance via mechanisms that likely involve regulation of AgRP neuronal survival and structure, and modulation of hypothalamic leptin action.